NETWORK DESIGN DECISION IN A CLOSED LOOP SYSTEM: LESSON LEARNED FROM ELECTRICITY DISTRIBUTION POLICY IN INDONESIA - Hidajat Hendarsjah; Wisnu Untoro; Reza Rahardian (Jurnal Aplikasi Bisnis dan Manajemen (JABM), 2020)
The article described the difficulty to spot specific suppliers that feed the targeted customers in a closed-loop supply chain. When managers had difficulties in identifying the role of suppliers in a supply chain network, several possible situations might appear, such as redundant supply that led to both over and undersupply situations. The article also portrayed a course of an evaluative process underlies the network design decisions in a closed-loop electricity supply system. The case research, as presented in the article, was based on an archival data examination, literature review, structured interviews, and observations on the field operations of the electricity distribution system in Indonesia’s main islands. The research findings revealed that the distribution network within the closed-loop supply chain system was suggested to implement two stages decisions; started with local optimization analysis and followed by unified solution among all local optimal solutions. Such an approach arguably would reduce redundant supply as well as minimizing both over and undersupply in the system. For practical implications the article demonstrated the possibility of drawing the false conclusion when transmission costs were ignored in the supply chain-design decision analysis, as exhibited in the Indonesia electricity supply network. Keywords: case research, closed loop supply chain, distribution channel, supply chain management, supply network Abstrak: Artikel ini menjabarkan kompleksitas yang dihadapi oleh para manajer ketika menetapkan konfigurasi pemasok yang dapat memenuhi permintaan konsumen dalam suatu sistem rantai pasokan tertutup. Masalah spesifik yang dihadapi oleh para manajer pada situasi tersebut adalah urusan pasokan berlebih maupun pasokan yang defisit. Untuk mengendalikan masalah-masalah tersebut artikel ini juga mendeskripsikan perlunya proses evaluatif dalam pengambilan keputusan pada sistem rantai pasokan tertutup. Demi mendapatkan solusi tersebut, penelitian berbasis kasus digunakan untuk mengelaborasi proses pengambilan keputusan yang dapat menghasilkan luaran yang efektif secara sistemik. Hasil penelitian menunjukkan bahwa keputusan dua tahap, yang diawali dengan optimasi di wilayah-wilayah regional dan diikuti dengan penyatuan optimasi untuk seluruh sistem rantai pasokan tertutup dapat mengurangi terjadinya pasokan berlebih maupun pasokan yang defisit. Pada tataran implikasi praktis, artikel ini juga mengulas terdapatnya peluang bagi para manajer untuk salah menyimpulkan tentang kualitas kinerja suatu sistem rantai pasokan tertutup, ketika mereka mengabaikan biaya transmisi, sebagaimana dihadapi pada jaringan distribusi listrik di Indonesia. Kata kunci: case research, closed loop supply chain, distribution channel, supply chain management, supply network